Robustness of spin-chain state-transfer schemes - Stolze, Joachim; Alvarez, Gonzalo Agustin; Osenda, Omar; Zwick, Analía Elizabeth (Springer, 2014)
Fil: Stolze, Joachim. Universität Dortmund; Alemania